O004 Inhibitory effect of an antiseptic mouthwash against Neisseria gonorrhoeae in the pharynx (GONE) among men who have sex with men: a randomised control trial. (30th June 2016) - Chow, Eric; Howden, Benjamin; Stevens, Kerrie; Walker, Sandra; Lee, David; Snow, Anthony; Cook, Stuart; Fehler, Glenda; Bradshaw, Catriona; Chen, Marcus; Fairley, Christopher
Abstract : Background/introduction: Gonorrhoea prevalence is increasing among men who have sex with men (MSM) worldwide. Studies suggest pharyngeal infection may be central to transmission and is the site of acquisition of resistant genes. With condom use falling, other interventions to reduce the transmission of gonorrhoea are urgently required. Aim(s)/objectives: To determine whether Listerine, a commercial mouthwash product, has an inhibitory effect against N. gonorrhoeae . Methods: MSM who tested positive for pharyngeal gonorrhoea by nucleic acid amplification test between May-2015 and February-2016 and returned for treatment within 14 days, were enrolled in the study. They were randomised to gargle either Listerine or saline for 60 seconds. Pharyngeal swabs were taken before and after gargling, and tested by culture. Only men who tested positive by culture before gargling were included in the analysis. The proportions of men who tested positive for pharyngeal gonorrhoea after gargling in both groups were calculated. Results: Of the 197 MSM who enrolled, only 58 MSM (33 in Listerine arm and 25 in saline arm) tested positive by culture on the day of recruitment. 17 (52%) MSM in the Listerine arm remained culture positive versus 21 (84%) in the saline arm after gargling the solution ( p = 0.013). The odds of being culture positive were 4.4 (95% CI: 1.4–17.7) times higher among men who gargled saline compared to those gargled Listerine. Discussion/conclusion: This data suggest Listerine could reduce the viable numbers of N. gonorrhoeae on pharyngeal surface which may prevent transmission. Further trials to look at efficacy over time are warranted.